GRAMMATICAL ERRORS IN BUSINESS STUDENTS' LEARNING CV WRITING - Nernere, Maria Setyaningsih (LATTE: A Journal of Language, Culture, and Technology ISSN 3063-0754, 2025)
Curriculum Vitae (CV) is an essential document used to showcase personal competence in written form. To make sure that competence is articulated correctly in a written format, students should be aware of their accuracy as it reflects their professionalism. Thus, this study aims to investigate the common grammatical errors found in CVs. Quantitative research was chosen. 34 random Business Economics students’ CV documents with a complete format were analyzed using a grammar checker tool named Grammarly. The result reveals that there were 221 grammatical errors found in the students’ CVs consisting of errors in lexis (34.56%), syntax (28.82%), discourse (23.53%), and morphology (16.67%). This finding highlights the students’ struggle to articulate their competence in a well-written document. Furthermore, this may be a reflection for students and teachers to attain better students writing in the future and for researchers to investigate more on grammar errors in the context of English for Foreign Learners and curriculum development of professional writing.